2003
DOI: 10.1523/jneurosci.23-20-07510.2003
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Cortical Neurons Respond to Somatosensory Stimulation

Abstract: The prevailing hierarchical model of cortical sensory processing holds that early processing is specific to individual modalities and that combination of information from different modalities is deferred until higher-order stages of processing. In this paper, we present physiological evidence of multisensory convergence at an early stage of cortical auditory processing. We used multi-neuron cluster recordings, along with a limited sample of single-unit recordings, to determine whether neurons in the macaque au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
224
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 304 publications
(242 citation statements)
references
References 40 publications
18
224
0
Order By: Relevance
“…These recent results were highly complementary to the pioneer works of Schroeder's laboratory that have revealed the multimodal feature of the monkey auditory belt where both visual and somatosensory responses can be evoked (Schroeder et al, 2001;Schroeder and Foxe, 2002;Fu et al, 2003). In the carnivore, while previous studies have reported that the visual cortex can be activated by auditory stimuli (Spinelli et al, 1968;Morrell, 1972;Fishman and Michael, 1973), intracellular recording in the primary visual cortex (A17) have recently failed to find such auditory responses (Sanchez-Vives et al, 2006).…”
Section: Electrophysiological Evidence In the Primary Sensory Areassupporting
confidence: 65%
“…These recent results were highly complementary to the pioneer works of Schroeder's laboratory that have revealed the multimodal feature of the monkey auditory belt where both visual and somatosensory responses can be evoked (Schroeder et al, 2001;Schroeder and Foxe, 2002;Fu et al, 2003). In the carnivore, while previous studies have reported that the visual cortex can be activated by auditory stimuli (Spinelli et al, 1968;Morrell, 1972;Fishman and Michael, 1973), intracellular recording in the primary visual cortex (A17) have recently failed to find such auditory responses (Sanchez-Vives et al, 2006).…”
Section: Electrophysiological Evidence In the Primary Sensory Areassupporting
confidence: 65%
“…The reported instances extend from somatosensory inputs to the cochlear nucleus through to bidirectional interactions between auditory and somatosensory cortex (16)(17)(18)(19)(20)(21)(22). There is also evidence that somatosensory inputs affect auditory perceptual function including cases involving speech (8,23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Physiological support for this hypothesis came from several studies in which sensitivity to spatial features was observed in the caudal belt, including CM (Recanzone, 2000;Recanzone et al, 2004;Recanzone et al, 2000b;Tian et al, 2001;Woods et al, 2006). Additional insight into the role of CM came from the discovery of multisensory integration in this area (Fu et al, 2003;Schroeder et al, 2001). A subpopulation of neurons in CM were found to be responsive to both auditory and somatosensory stimulation.…”
Section: The Role Of CM In Auditory Cortical Processingmentioning
confidence: 97%